Time-dependent deformation and fracture evolution around underground excavations. Issue 1 (1st December 2020) - Fu, Teng-Fei; Xu, Tao; Wasantha, P.L.P.; Yang, Tian-Hong; Nara, Yoshitaka; Heng, Zhen
Abstract: A numerical time-dependent deformation model of rock by incorporating the stress corrosion model into a three-dimensional discrete element code was established to investigate time-dependent deformation and fracture evolution of surrounding rock around underground excavations with circular, inverted U-shaped and rectangular cross-sections. The mesoscale model input parameters were calibrated to replicate the mechanical behavior and failure patterns of the rock observed in laboratory. Numerical simulations on the time-independent and -dependent deformation and fracturing evolution of the rock around underground excavations with different shapes under hydrostatic stress were studied. The results show that the maximum time-independent displacements of circular, inverted U-shaped and rectangular openings are 11, 15, and 34  mm at left roof, right floor and left side, respectively. It shows that the surrounding rocks around the circular, inverted U-shaped openings are much more stable than that around the rectangular opening. The cracks within the surrounding rock around different shaped openings gradually increases as time goes by, and the tensile cracks are dominant. The progressive failure process of the circular openings under varying lateral pressures was further modeled. The results show the failure zone at the roof wall and floor wall becomes more evident with an increase in the lateral pressure coefficient.